Effectiveness of Arabic Language Learning With Imla’ Mandhur Method On Maharah Kitabah (Arabic Writing Skills) Of Grade VII Students Of MTs Al-Ghozaly Siwatu Watumalang Wonnosobo - Qothrun Nada, Royani; Sunarko, Asep; Linnaja, Ngatoillah (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
This aims to: 1) Apply the imla’ mandhur method to increasing understanding of the book in class VII students at MTs Al-Ghozaly Siwatu Watumalang Wonosobo; 2) Knowing the effectiveness of the imla’ mandhur method on maharah kitabah for class VII students at MTs Al-Ghozaly Siwatu Watumalang Wonosobo; 3) Understand the differences in maharah kitabah (Arabic writing skills) between classes that apply and classes that do not apply the imla’ mandhur method for class VII students at MTs Al-Ghozaly Siwatu Watumalang Wonosobo. This thesis uses a quantitative approach where the type of research is field research. Data collection techniques use observation, interviews, documentation and tests. The analysis techniques used are normality test, homogeneity test, gain test, t test. The research results show that; 1) Learning The concept of the imla’ mandhur method in learning Arabic in class is that students are given material, then students pay attention, see and understand the material. 2) The process of learning Arabic using the imla’ mandhur method for maharah kitabah (Arabic writing skills) starts with the teacher giving material to students, the teacher writes it on the blackboard then the students pay attention to what the teacher wrote, then the teacher erases the writing on the blackboard, the teacher dictates the mufrodat that has been delivered earlier and the students are asked to write it in their respective books. 3) From the results of hypothesis testing with the Gain Test (N-gain), it shows that there is an increase in the Maharah Kitabah learning outcomes for students in class VII C as the experimental class by 0.788 and class VII D as the control class by 0.241. The experimental class is superior to the control class, because the experimental class has higher scores. This proves that the imla’ mandhur method is effective in maharah kitabah (Arabic writing skills) in learning Arabic.